Wolf-Parkinson-White syndrome in young men presenting with palpitation: the pattern of delta waves in predicting location of accessory pathway (Faculty of Medicine Universitas Indonesia, 2011)
Palpitation is a common presenting symptom in the emergency department. Wolf-Parkinson White (WPW) syndrome is a cardiac conduction disorder that may present with palpitation and lead to sudden cardiac death. WPW could be detected byÂ electrocardiogram (ECG). In this case report, we present two young male patients with WPW syndrome admitted to our hospital with history of repeated and progressive palpitation. ECG of the first patient revealed supraventricular tachycardia which converted to sinus rhythm after propanolol treatment. ECG showed sinus rhythm with delta wave in lead II,III,aVF, V1 suggesting the presence of accessory pathway (AP) in left lateral wall. Electrophysiology study confirmed the presence of AP and radio frequency catheter ablation was successfully done resulted in disappearance of delta on outpatient clinic ECG. Patient has no symptom and he do not have to take medication. ECG of the second patient revealed supraventricular tachycardia with abberancy. After amiodarone infusion, ECG showed sinus rhythm with delta wave in lead I,II,aVL suggesting the presence of accessory pathway in anteroseptal wall. Electrophysiology study and catheter ablation did not perform for this patient because of financial problem, however amidarone has to be taken regularly to prevent the recurrence of supraventricular tachycardia. (Med J Indones 2011; 20:298-301)Keywords: ECG, palpitation, supraventricular tachycardia, Wolf- Parkinson White syndrome